Developing The Initial Flight Attendant Students’ Speaking Skills Using Problem-Based Learning Technique - Kusumoriny, Laksmy Ady (CV. Pena Persada, 2018)
The objectives of this study are(1) To identify the most common communication problems found by the flight attendants in the real-life working situation, (2) To investigate how problem-based learning technique can be used to develop the students‘ speaking skills, and (3) To analyze what the development of the students‘ speaking skills is. The subjects were 24 initial flight attendant students who attended the initial English class in Garuda Indonesia Training Center. The instruments employed in this study are interviews, observations and support by the documentation.